Transcutaneous application of oil and prevention of essential fatty acid deficiency in preterm infants. Issue 1 (January 1993) - Lee, E J; Gibson, R A; Simmer, K
Abstract : The topical application of vegetable oil was assessed as an alternative means of providing essential fatty acids (EFA) to parentally fed preterm infants who were not receiving lipid. Three infant pairs ranging in gestational age from 26-32 weeks were studied. Safflower oil or safflower oil esters (1 g linoleic acid/kg/day) were applied to available areas daily. All infants rapidly developed biochemical EFA deficiency. The plasma fatty acid profiles were similar in infants with or without topical oil, and all returned to normal once parenteral lipid was introduced. We found no evidence to suggest that the transdermal route is of use in the nutritional management of preterm infants.